STRATEGIC MANAGEMENT OF POULTRY FARMING IN NORTHERN MALAYSIA: A CASE STUDY ON RURAL COMMUNITY IN KEDAH: Received: 19th December 2023; Revised: 23rd December2023, 03rd January 2024; Accepted: 05th January 2024 - Mohamed Ismail, Risyawati; Mustafar, Mastora; Abu Bakar, Siti Zakiah (LIFE: International Journal of Health and Life-Sciences, 2024)
The rural agriculture sector in Malaysia is vital to the economy because it employs many. Agriculture employs 3.5 million Malaysians and amounts for 9.1% of GDP, according to Statistics Malaysia (2019). Malaysian poultry farming is vital to rural income and jobs. Poultry farmers must grasp market dynamics and prepare strategically to succeed in animal production. A socioeconomically challenged group was used to evaluate rural Malaysian chicken raising practices. The case study demonstrated how these principles apply pragmatically to similar groups. The study collected qualitative data via in-person interviews. Interview covered poultry producers' issues and data was analyzed accordingly. Results indicated that lack of extension agents, technical expertise, budgetary constraints, and communication infrastructure hinder poultry breeding farmers. These challenges drove them to forsake their poultry farm and focused on rubber tapping as the main source of income. The latter strategy is less profitable but less laborious and cheaper. The study analyzed how community empowerment sustains rural development. To enhance rural areas, policymakers and development practitioners must understand community-led activities and create focused policies. Further research should study how government agencies might boost rural economic activity and supply chain efficiency.